In the adjoining figure AB=AD and CB=CD, Prove that
ΔABC≅ΔADC
Attachments:
![](https://hi-static.z-dn.net/files/dbd/f25b1218a22dcd61cbe231ade76334fb.jpg)
Answers
Answered by
1
Answer:
Given, AB = AD and CB = CD
To prove, ΔABC ≅ ΔADC.
Proof, In ΔABC and ΔADC
AB = AD (given)
CB = CD (given)
AC = AC (common)
∴ ΔABC ≅ ΔADC. (By SSS congruence property)
Answered by
0
Step-by-step explanation:
i hope this is useful to you
Attachments:
![](https://hi-static.z-dn.net/files/d3f/f3d345b263622f2b93984fb4d5984586.jpg)
Similar questions